Don't look twice - Gross, Andrew 1952- (William Morrow, 2009)
After a drive-by shooting in Greenwich, Connecticut, nearly kills him, Hauck follows the trail to a sinister gambling scheme at an upstate casino and is caught in a deadly maze of cover-up and corruption.